Finansowanie rzeczowych aktywów trwałych z budżetu państwa (na przykładzie uczelni publicznych) - Wasilewski, Mirosław; Pisarska, Aleksandra (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The aim of this paper is to find out determinants and options for purchasing fixed assets in state-operated institutions of higher education financed by the State Treasury. Based on applicable law that regulates the possibility of State Treasury’s financing of purchase or unaided production of fixed assets in public institutions of higher education, a detailed analysis was performed. An examination of the currently valid method and a procedure of fixed assets financing revealed difficulties encountered by institutions of higher education in the course of investments financed with State Treasury funds. Applicable statutory regulations concernig the limitation of financing of fixed assets with a subsidy specifically designated for the purchase or production of fixed assets contain significant complications, thus restricting operations and development of institutions of higher education. Values provided in taxation law, allowing for one-off depreciation or introducing limits for one-off depreciation are applicable to certain values, different groups of fixed assets and different businesses (that pay income tax). An institution of higher education is not a payer of income tax and as such it makes use of balance sheet regulations only (based on accounting policy), and it does not make use of tax policy. Tax reliefs do not impact on effectiveness of management of resources of an institution of higher education, and recording of one-off depreciation of fixed assets with a final value below an amount allowed for such depreciation results in the deformaion of financial result and economic/financial image of such an institution.